Utilising CRISPR-Cas9 mediated genome editing to C-terminally tag endogenous gene loci with fluorescent protein fusions in preimplantation mouse embryos - Pekľanská, Miriama (Jihočeská univerzita, 2021)
Master´s thesis demonstrates the C-terminally fluorescent tagging of endogenous genes in the preimplantation mouse embryos by utilizing CRISPR-Cas9 mediated genome editing method.
Utilising CRISPR-Cas9 mediated genome editing to C-terminally tag endogenous gene loci with fluorescent protein fusions in preimplantation mouse embryos
Keywords: mouse preimplantation developmental stages; the first cell-fate decision; the second cell-fate decision; mCherry; WWC2; p38-Mapks; CRISPR-Cas9; fluorescent C-terminal tagging.; mouse preimplantation developmental stages; the first cell-fate decision; the second cell-fate decision; mCherry; WWC2; p38-Mapks; CRISPR-Cas9; fluorescent C-terminal tagging.